Becoming subject. Subjectivity and individualization in the philosophy of E. Paci (Nóema, 2013)
In this paper we describe the theory of subjectivity elaborated by Enzo Paci through his study of Husserl’s phenomenology. The investigation of the subject’s pre-categorial dimension brings the author to develop a concept of subjectivity as infinite aim (telos). This topic can be put in the wider context of a rethinking of philosophy as practice of transformation of reality.
Keywords: Subject; subjectivity; Paci; Husserl; phenomenology; relation; substance; identity; truth